Developing fundamental programming concepts and computational thinking with ScratchJr in preschool education: a case study. (2016) - Papadakis, Stamatios; Kalogiannakis, Michail; Zaranis, Nicholas
In recent years, the teaching of programming and development of fundamental programming concepts at the preschool age has attracted the interest of the educational and scientific community. International research has highlighted that teaching programming to young children has a crucial influence on the development of their cognitive functions. There are currently plenty of available programming environments suited for preschoolers. Researchers are adapting their views concerning the age threshold at which young children can effectively get involved with programming. A new programming environment, which was designed to help preschoolers familiarise with basic programming concepts, in a developmentally appropriate manner, is ScratchJr. This study performs a brief introduction to the characteristics of ScratchJr as well as a presentation of the results of a small-scale pilot study for the evaluation of ScratchJr as means of teaching basic programming concepts in the preschool classroom.